Odnosi z učitelji in zaznana opora vrstnikov kot dejavnik medvrstniškega nasilja (Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije, 2025)
Teachers are important builders of a sense of safety and acceptance in the classroom and are therefore key in preventing and reducing peer violence. The paper explores the positive and negative aspects of students' relationships with teachers and the role of peer support in experiencing and perpetrating peer violence over a school year. The data show a significant increase in the perpetration (but not the experience) of peer violence over the school year and the important role of contexts, i.e. teacher and peer. Students who report more positive and less negative aspects of relationships with teachers report less perpetration and perpetration of peer violence. Students with more peer support report less experience of peer violence. In the recommendations for practice, we emphasize strengthening teachers' relational competence and social and emotional learning in classrooms.